The Role of Open Records Accounting Technology in Supporting Supply Chain Management to Achieve Competitive Advantage: Survey Study: The Opinions of a Sample of Accountants, Auditors and Financial Managers in a Sample of Industrial Companies Operating in Sulaymaniyah Governorate - مجيد نجم, بصيرة; كاوانى أسعد, بينايى (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The research aims to identify the concept of openbook accounting technology , explain its importance, define its dimensions, and indicate the effects it causes on the practices of supply chain management, and clarify the theoretical framework for openbook accounting technology and supply chain management, and this contributes to a statement of the ways to benefit from them in achieving competitive advantage. Through this research, it is possible to highlight the importance of openbook accounting technology, and to clarify the positive effects that can be reached in the event of completion of its application between the parties involved in the supply chains, and to strengthen the strategic relationship between industrial companies and their customers in order to achieve competitive advantages that ensure their continuity in the business environment. To achieve the objectives of the research, the researcher relied on the analytical description and the field survey to obtain data from its main sources by relying on a questionnaire designed to achieve the objectives of this research, then distributed it to a sample of accountants, auditors and financial managers in a sample of industrial companies operating in Sulaymaniyah Governorate, and to analyze the results of the field side. The two researchers relied on the results of the analysis of the program (SPSS VE 24 & SMART PLUS). Among the most important results of the research: the existence of a statistically significant relationship between the openbook accounting technology and the competitive advantage of (0.586), and the presence of an indirect, statistically significant effect of the openbook accounting technology (OBAT) on the competitive advantage through supply chain management as an intermediate variable, that is, the management variable The supply chain mediates the relationship between two variables: openbook accounting technology and competitive advantage. The research recommended the need to apply openbook accounting technology because it contributes to achieving competitive advantages for industrial companies, keeping pace with emerging environmental development, and opening books for partners within supply chains, which helps achieve and sustain a competitive advantage.